CESifo World Economic Survey February 2013 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Tim Oliver Berg (CESifo World Economic Survey, 2013)
World Economic Climate: World Economic Climate improves - Economic Expectations: Economic expectations predominantly positive - Inflation: Price increase expected to slow down - Currencies: Moderate rise of US dollar expected - Interest Rates: Sligthly higher long-term interest rates expected - Special Topic: SMEs and their importance to the economy
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies